2015
DOI: 10.4238/2015.december.28.38
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of serum DKK-1 predicts poor prognosis in patients with papillary thyroid cancer

Abstract: ABSTRACT. The Wnt inhibitor dickkopf-1 (DKK-1) has been shown to be closely correlated with tumor initiation and progression in various types of cancers. However, the serum level of DKK-1 in patients with papillary thyroid cancer (PTC) and its potential clinical significance is poorly understood. Enzyme-linked immunosorbent assay (ELISA) was used to evaluate the level of serum DKK-1 in patients with PTC (N = 132) and healthy controls (N = 40). The association between serum DKK-1 level and clinicopathological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…However, how cancer cells evade negative regulation of Wnt/ β -catenin signaling and establish constitutive β -catenin/TCF activation remains unclear. Most importantly, our results established DKK1, a negative regulator of Wnt signaling, as a direct functional effector of miR-373-3p in TSCC, which is in agreement with many studies showing that DKK1 is downregulated in various cancers [3032]. So far, how DKK1 functions and regulates in TSCC remains unclear.…”
Section: Discussionsupporting
confidence: 91%
“…However, how cancer cells evade negative regulation of Wnt/ β -catenin signaling and establish constitutive β -catenin/TCF activation remains unclear. Most importantly, our results established DKK1, a negative regulator of Wnt signaling, as a direct functional effector of miR-373-3p in TSCC, which is in agreement with many studies showing that DKK1 is downregulated in various cancers [3032]. So far, how DKK1 functions and regulates in TSCC remains unclear.…”
Section: Discussionsupporting
confidence: 91%
“…However, it was reported that DKK1 inhibited the survival and migration of TC cells by repressing Wnt/β‐catenin signaling pathway 41 . Downregulation of DKK1 prediected poor prognosis in thyroid cancer 42 . These results were consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…DKK2 generally acts as a negative regulator of canonical WNT signaling, depending on the cellular context 47 . A related family member, DKK1, has been shown to inhibit thyroid cancer survival 48 and its downregulation correlates with poorer prognosis in PTC 49 . Furthermore, we also observed significant upregulation of EGFR upon knockdown of EPB41L4A.…”
Section: Discussionmentioning
confidence: 99%